Effects of increased dietary lysine on sow and litter performance - Musser, R.E.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred arid fifty three lactating sows were used to determine the effects of increased dietary lysine on sow and litter performance. At farrowing, sows were assigned to com-soybean meal lactation diets consisting of either 1.0 or 1.3% total lysine. A treatment by parity interaction was observed, with first parity sows fed 1.3% lysine having heavier litter weaning weights than sows fed 1.00/0 lysine. Surprisingly, third and fourth parity sows fed 1.3% lysine had lower litter weaning weights than those fed 1.0% lysine. No other treatment by parity interactions existed. No differences were observed in the number of pigs weaned or pig survivability. Sows fed 1.3 % lysine tended to consume less feed in the first week of lactation than sow fed 1.0% lysine (9.6 vs 10.0 Ibid), with no differences observed during week 2 or overall. No differences were observed in subsequent performance of the sows on days to estrus; farrowing rate; or number of pigs born, born alive, stillborn, or born mummified. This experiment showed that increasing dietary lysine from 1.0% to 1.3% increased litter weaning weights for parity 1 sows but not for older sows.
Keywords: Swine; Lysine; Lactation; Weaning weight; Sows